Somatic inactivation of the VHL gene in Von Hippel-Lindau disease tumors. - Prowse, A H (1997)
Von Hippel-Lindau (VHL) disease is a dominantly inherited disorder predisposing to retinal and CNS hemangioblastomas, renal cell carcinoma (RCC), pheochromocytoma, and pancreatic tumors. Interfamilial differences in predisposition to pheochromocytoma reflect allelic heterogeneity such that there is a strong association between missense mutations and risk of pheochromocytoma. We investigated the mechanism of tumorigenesis in VHL disease tumors to determine whether there were differences between tumor types or classes of germ-line mutations. Fifty-three tumors (30 RCCs, 15 hemangioblastomas, 5 pheochromocytomas, and 3 pancreatic tumors) from 33 patients (27 kindreds) with VHL disease were analyzed. Overall, 51% of 45 informative tumors showed loss of heterozygosity (LOH) at the VHL locus. In 11 cases it was possible to distinguish between loss of the wild-type and mutant alleles, and in each case the wild-type allele was lost. LOH was detected in all tumor types and occurred in the presence of both germ-line missense mutations and other types of germline mutation associated with a low risk of pheochromocytoma. Intragenic somatic mutations were detected in three tumors (all hemangioblastomas) and in two of these could be shown to occur in the wild-type allele. This provides the first example of homozygous inactivation of the VHL by small intragenic mutations in this type of tumor. Hypermethylation of the VHL gene was detected in 33% (6/18) of tumors without LOH, including 2 RCCs and 4 hemangioblastomas. Although hypermethylation of the VHL gene has been reported previously in nonfamilial RCC and although methylation of tumor-suppressor genes has been implicated in the pathogenesis of other sporadic cancers, this is the first report of somatic methylation in a familial cancer syndrome.